2014
DOI: 10.1603/an13047
|View full text |Cite
|
Sign up to set email alerts
|

Two Species withinDendroctonus frontalis(Coleoptera: Curculionidae): Evidence from Morphological, Karyological, Molecular, and Crossing Studies

Abstract: Dendroctonus frontalis Zimmermann is considered one of the most important economic and ecological forest pests in the United States, Mexico, and Central America. Recently, two apparent morphological variants of this species were discovered occurring syntopically in Central America and southern Mexico. Morphotype A beetles lack a series of fine parallel ridges on the episternal area of the prothorax that are present on morphotype B. The goal of the present work was to clarify the taxonomic status of the morphot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…Cross-mating experiments among D. frontalis populations from the southeastern United States, Arizona, and Nuevo Leon, Mexico as well as from Texas and Honduras (Lanier et al, 1988;Vit e et al, 1974) suggest the lack of post-mating reproductive isolation mechanisms among these populations. Furthermore, consistency in seminal rod morphology and karyotype further supports the validity of D. frontalis as a single species throughout its extensive range (Armendáriz-Toledano et al, 2014;Lanier et al, 1988). However, there is evidence of some variation in pheromone production within the species.…”
Section: Geographic Variationmentioning
confidence: 62%
See 2 more Smart Citations
“…Cross-mating experiments among D. frontalis populations from the southeastern United States, Arizona, and Nuevo Leon, Mexico as well as from Texas and Honduras (Lanier et al, 1988;Vit e et al, 1974) suggest the lack of post-mating reproductive isolation mechanisms among these populations. Furthermore, consistency in seminal rod morphology and karyotype further supports the validity of D. frontalis as a single species throughout its extensive range (Armendáriz-Toledano et al, 2014;Lanier et al, 1988). However, there is evidence of some variation in pheromone production within the species.…”
Section: Geographic Variationmentioning
confidence: 62%
“…Little research has been done on the role of D. frontalis pheromones in mediating reproductive isolation from closely related species, although several such species may occupy the same portions of hosts (ie, exist in syntopy), utilize the same aggregation pheromone components, and be capable of pairing in the laboratory (Armendáriz-Toledano et al, 2014Davis and Hofstetter, 2009;Hofstetter et al, 2008Hofstetter et al, , 2012Lanier et al, 1988;Moser et al, 2005;Niño-Domínguez et al, 2015a;Sullivan et al, 2012). In olfactometer studies of D. frontalis and its sibling D. mesoamericanus which jointly colonize the same hosts in the Central American region, it was found that males could readily distinguish odours of conspecific and heterospecific female gallery entrances, and ipsdienol and endo-brevicomin (compounds produced by D. mesoamericanus but not D. frontalis females) were identified as the species-specific cues that mediated this discrimination (Niño-Domínguez et al, 2015a).…”
Section: Pheromones In Reproductive Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…In laboratory crossing studies, confinement of males of D. frontalis and D. mesoamericanus over gallery entrances of heterospecific females resulted in pairing, sperm transfer, gallery formation, egg laying, and development of larvae, although measures of pairing success, such as frequency of sperm transfer, gallery length, and brood production were generally less in heterospecific than conspecific pairings (Armendáriz-Toledano et al 2014). Hybrid viability and fertility were not tested because the authors have, as yet, been unable to rear brood of either conspecific or heterospecific pairings to adulthood in the laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid viability and fertility were not tested because the authors have, as yet, been unable to rear brood of either conspecific or heterospecific pairings to adulthood in the laboratory. However, differing chromosome numbers between the two species suggest that post-zygotic reproductive isolation exists (Armendáriz-Toledano et al 2014). Despite the ability to force heterospecific pairings in the laboratory, dissections of naturally infested pines in Chiapas, Mexico have failed to reveal the presence of heterospecific pairs within zones of species overlap on the bark (Niño et al unpublished data).…”
Section: Introductionmentioning
confidence: 99%